The development of drugs against Acanthamoeba infections - Siddiqui, Ruqaiyyah Bano *; Aqeel, Yousuf; Khan, Naveed Ahmed * (American Society for Microbiology, 2016)
For the past several decades, there has been little improvement in the morbidity and mortality associated with Acanthamoeba keratitis and Acanthamoeba encephalitis, respectively. The discovery of a plethora of antiacanthamoebic compounds has not yielded effective marketed chemotherapeutics. The rate of development of novel antiacanthamoebic chemotherapies of translational value and the lack of interest of the pharmaceutical industry in developing such chemotherapies have been disappointing. On the other hand, the market for contact lenses/contact lens disinfectants is a multi-billion-dollar industry and has been successful and profitable. A better understanding of drugs, their targets, and mechanisms of action will facilitate the development of more-effective chemotherapies. Here, we review the progress toward phenotypic drug discovery, emphasizing the shortcomings of useable therapies.